2018
DOI: 10.1007/s10905-018-9662-4
|View full text |Cite
|
Sign up to set email alerts
|

Aphids Playing Possum – Defensive or Mutualistic Response?

Abstract: Paper presents the phenomenon of thanatosis or death-feigning in selected aphids species. This specific reaction was predominantly analysed on the example of aphid subfamily Lachninae. Individuals of this group were used in experiments, during which a thanatotic response was induced with various results. The response differed from prolonged thanatosis, lasting for several minutes (Eulachnus rileyi), through shrinking behaviour (e. g. in Stomaphis graffii) to non-responsive species such as Cinara (Schizolachnus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Batch effects (differences from plant to plant) and sub-line specific variation also can add more variation to developmental rates. Additionally, aphids are known to have a behavioral alarm response to plant vibrations causing them to drop off of the plant [57,58,59,60,61]. Plant handling during molt checking (while done delicately), potentially could have triggered this response, which again could unevenly add time to the development of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Batch effects (differences from plant to plant) and sub-line specific variation also can add more variation to developmental rates. Additionally, aphids are known to have a behavioral alarm response to plant vibrations causing them to drop off of the plant [57,58,59,60,61]. Plant handling during molt checking (while done delicately), potentially could have triggered this response, which again could unevenly add time to the development of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Hölldobler & Wilson, 1990). Some aphid species show thanatotic responses (death feigning), probably to reduce aggressiveness of ants (Bilska et al ., 2018).…”
Section: Evolution Of Communicationmentioning
confidence: 99%
“…Some insects make severe sounds and inaudible vibrations, or feign death to avoid predation. A recent study reported that feigning death has been observed in a number of aphid species, especially in the subfamily Lachninae [36]. Some insects mimic an unfavorable and dangerous organism, such as a scorpion (e.g., phasmids) [3,37,38] or slightly eusocial soldier aphids (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%